THE EFFECT OF GOVERNMENT REGULATION NUMBER 55 OF 2022 AND TRUST IN GOVERNMENT ON COMPLIANCE OF SME TAXPAYERS IN SUBANG DISTRICT - Feby Farichatul Ummah; Tanzil Alfadhilatunnisa (Journal of Taxation Analysis and Review, 2024)
Taxes have a function as a source of revenue for the government which is used to finance both routine and development expenditures. This study aims to determine the effect of the implementation of government regulation No. 55 of 2022 and trust in government on MSME taxpayer compliance in Subang Regency. The type of research used in this research is quantitative method. The population in this study were all MSME taxpayers in Subang Regency. The sample of respondents in this study was adjusted to 100 MSME taxpayers in Subang Regency using incidental sampling techniques which are included in nonprobability sampling. The data used is primary data, collected using a questionnaire filled out directly by the respondent. Some tests that will be carried out include descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression tests, and data hypothesis tests which include t tests, F tests and coefficient of determination tests. The results of this study indicate that PP Number 55 of 2022 policy has a significant effect on MSME taxpayer compliance in Subang Regency. Meanwhile, trust in the government has no effect on MSME taxpayer compliance in Subang Regency.